UPAYA KEPOLISIAN DALAM PENCEGAHAN COVID-19 DI LUBUKLINGGAU (STUDI PERANAN BHABINKAMTIBMAS KELURAHAN TABA LESTARI) - Amra Muslimin (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the role of Bhabinkamtibmas in Taba Lestari Village in preventing Covid-19. Limitation of the problem in research on Police efforts in preventing Covid-19 in Lubuklinggau (Study on the Role of Bhabinkamtibmas, Taba Lestari Village). This research uses descriptive qualitative research method. The data source related to this problem is the Police Efforts in preventing Covid-19 in Lubuklinggau (Study on the Role of Bhabinkamtibmas, Taba Lestari Village). Data collection methods in this study were observation, interviews and documentation. The aspects of this research are protection, protection and service to the community. Based on research from the aspect of protection, protection and service to the community, monitoring and evaluation as well as socialization and participation in the prevention and control of Covid-19. The role played by Bhabinkamtibmas has been well realized in Taba Lestari Village